Examining NDVI Trends in Serang City to Assess Vegetation Changes between 2019 and 2023 - Nihan, Aditya Rahman Kintu; Rachmawati, Dian; Firdaus, Najmi (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
This study examines changes in the Normalised Difference Vegetation Index (NDVI) for Serang City between 2019 and 2023 to quantify vegetation density and health in the face of urbanization. Using Sentinel-2 satellite data and GIS analysis, it investigates how urban development, climate change, and land use influence plant cover. The findings indicate a substantial decrease in high vegetation from 13,089.791 hectares in 2019 to 12,296.742 hectares in 2023, accompanied by increases in tiny vegetation and aquatic zones. Statistical experiments show that urban expansion is a significant cause of vegetation loss, with climate changes impacting sparsely vegetated areas. This study emphasizes the dynamic interplay between urban expansion and climate conditions in generating vegetation trends, providing essential information for urban planners and politicians. The results demonstrate the necessity for focused reforestation and sustainable urban development to save green places, enhance environmental quality, and alleviate the adverse effects of urbanization. Immediate urban planning initiatives are recommended to combat vegetation loss, promote sustainable development, and increase resistance to environmental change.